2019
DOI: 10.7185/geochemlet.1917
|View full text |Cite
|
Sign up to set email alerts
|

182W evidence for core-mantle interaction in the source of mantle plumes

Abstract: Tungsten isotopes are the ideal tracers of core-mantle chemical interaction. Given that W is moderately siderophile, it preferentially partitioned into the Earth's core during its segregation, leaving the mantle depleted in this element. In contrast, Hf is lithophile, and its short-lived radioactive isotope 182 Hf decayed entirely to 182 W in the mantle after metal-silicate segregation. Therefore, the 182 W isotopic composition of the Earth's mantle and its core are expected to differ by about 200 ppm. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
142
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(167 citation statements)
references
References 5 publications
6
142
4
Order By: Relevance
“…This correlation can indicate core-mantle interaction with transfer of the high 3 He/ 4 He and low 182 W signature of the outer core to the source of the OIBs. A similar conclusion was reached in a more recent study by Rizo et al (2019) where they found that core-mantle exchange might be facilitated by exsolution of W-rich, Si-Mg-Fe oxides from the core into the mantle. A correlation between the highest 3 He/ 4 He values and the highest 186 Os/ 188 Os ratios in Hawaii was also used as an evidence for a core contribution to He and Os (Walker et al, 1995).…”
supporting
confidence: 83%
“…This correlation can indicate core-mantle interaction with transfer of the high 3 He/ 4 He and low 182 W signature of the outer core to the source of the OIBs. A similar conclusion was reached in a more recent study by Rizo et al (2019) where they found that core-mantle exchange might be facilitated by exsolution of W-rich, Si-Mg-Fe oxides from the core into the mantle. A correlation between the highest 3 He/ 4 He values and the highest 186 Os/ 188 Os ratios in Hawaii was also used as an evidence for a core contribution to He and Os (Walker et al, 1995).…”
supporting
confidence: 83%
“…Heterogeneities in 142 Nd/ 144 Nd appear to be rare in modernday igneous rocks (2,5,7,11,13,(25)(26)(27), to the degree they occur for 182 W/ 184 W (30,31), which sometimes occur in the samples with lack of 142 Nd/ 144 Nd variability (32). Although the short-lived Sm-Nd and Hf-W systems are affected during silicate-mantle differentiation, the lack of isotopic variability in one system over the other, suggests the decoupling of the two systems owing to different processes involved in the generation of heterogeneity.…”
Section: Significancementioning
confidence: 99%
“…Furthermore, because 129 Xe/ 130 Xe ratios in the plume and MORB sources are distinct in the modern‐day mantle, the two sources must have remained separated for at least the past 4.45 billion years (Mukhopadhyay, ; Pető et al, ). Similarly, isotopic anomalies in 182 W (due to the decay of 182 Hf) have also been observed in low 4 He/ 3 He materials (Mundl et al, ; Rizo et al, ). Given its even shorter half‐life, 182 W anomalies in low 4 He/ 3 He materials (Mundl et al, ; Rizo et al, ) require that the low 4 He/ 3 He reservoir was generated no later than 60 million years after solar system formation (though we do note that the validity of some tungsten isotope data in low 4 He/ 3 He materials is still debated; Kruijer & Kleine, ; Rizo et al, ).…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, isotopic anomalies in 182 W (due to the decay of 182 Hf) have also been observed in low 4 He/ 3 He materials (Mundl et al, ; Rizo et al, ). Given its even shorter half‐life, 182 W anomalies in low 4 He/ 3 He materials (Mundl et al, ; Rizo et al, ) require that the low 4 He/ 3 He reservoir was generated no later than 60 million years after solar system formation (though we do note that the validity of some tungsten isotope data in low 4 He/ 3 He materials is still debated; Kruijer & Kleine, ; Rizo et al, ). The timing of the Moon‐forming giant impact is still debated, although recent isotopic studies (Barboni et al, ) constrain Moon formation to between 50 and 60 million years after the start of the solar system (Barboni et al, ; Touboul et al, ).…”
Section: Discussionmentioning
confidence: 78%